Financialisation and innovation in emerging economics: Evidence from Brazil - Halima Jibril; Annina Kaltenbrunner; Effi Kesidou (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2018)
This article contributes to the literature on the financial constraints of innovation in two ways. First, we examine whether financialisation has transformed the relation between finance and innovation by assessing the association between companies' financial relations, both on the liability side and the asset side of their balance sheets, and intangible assets. Second, this is the first study that examines theoretically and empirically the link between financialisation and innovation in the context of emerging markets using the population of publicly listed companies in Brazil over the period 2011-2016. We find evidence that whilst financial liabilities do not affect investments on intangibles, higher financial assets and financial profits discourage investments on intangibles. Other indicators of financialisation are not significant. Thus, our results support the crowding-out hypothesis that financialisation i.e. companies' increased tendency to hold financial assets and generate revenue from financial income rather than their underlying operations, discourages investments on innovation.
Keywords: 330; Financialisation; Intangible assets; Innovation-driven growth; Emerging economies